Kepemimpinan Dan Manajemen Organisasi Inovatif Di Era Disrupsi Dengan Semangat Budaya Anti Korupsi - Yudhi Novriansyah; Herawati Herawati; Supriyati Supriyati; Darham Wahid; Khairun A Roni (Jurnal Kabar Masyarakat, 2024)
To improve leadership and management skills and spreading an anti-corruption culture in the younger generation. The working group for reviewing socio-cultural issues at the Muara Bungo University Research and Community Service Institute (LPPM) in collaboration with the Muara Bungo Treasury Services Office (KPPN) held a Seminar on Innovative Organizational Leadership and Management in the Era of Disruption with the Spirit of Anti-Corruption Culture. This Seminar involves organizational elements of the Student Executive Board (BEM) and the Intra-School Student Organization (OSIS) in Bungo Regency and expected to inspire the younger generation to be more enthusiastic in learning and working in all fields in order to realize the Vision of a Golden Generation 2045 that is quality, competent and empowered in high competition.